Clinical legal education and cultural relativism- the realities in the 21st century (2014)
‘Ubi jus ibi remedium’ is a Latin maxim that means ‘where there is a wrong, there is a remedy’. Human rights are expected to be universal and applicable to every human being. In reality not all rights guaranteed in the International Instruments are applicable in some African societies with different culture, religion and norms. Culture shapes the identity of people generally in Africa and elsewhere thus the issue of Cultural Relativism is germane to the very existence of people of African descent. International Convention and Instruments provide for Women’ Rights generally and particularly the Right to life. The experience in the Women’s Law Clinic (the clinic) of the University of Ibadan has shown the imbalance between Clinical Legal Education (CLE) and the realities in practice. This paper considers the cultural practices in some societies in Nigeria, the techniques of CLE adopted in the clinic and the challenges of the 21st Century.